Developing computational thinking best practices for early childhood education in Kuwait and United States - Malallah, Safia A O E A (Kansas State University, 2022)
There are many concerns from early childhood educators regarding allowing children to use technology, pointing to the adverse effects of screen time and barriers such as lack of resources. To support advocating CT in early childhood settings using technology, this dissertation proposes solutions and resources for early childhood educators by highlighting the best practices in using technology as a medium for children to grow and learn while working through the adverse effects. The contribution of this work developed a "bes-T-ech" framework that has been used to develop two programs created based on the gaps in literature reviews. The first one relates to integrating CT into non-CS disciplines, namely drama. The lesson learning objective was delivered using robotic activities with the aim to create a template that can be used as a sample for other educators to align their lessons with CT standards. The second program teaches CT using our suggested Computational Thinking Pedagogical + Framework. The chosen environment is a virtual world (VW) due to the few studies or resources linking early childhood education and VW. Accordingly created a CT VW blueprint. By the same token, three reinforcement experiments were executed to advocate CT into Kuwaiti society. The reinforcements were complemented with a developed STEM model designed to meet the needs of Arabic/Persian Gulf region learners. The first reinforcement investigates the educators' CT awareness and proposes a plan for implementing CT into the Kuwaiti education system. The second reinforcement transferred a successful CT outreach program from a Western country into Kuwait, which brought insight into the CT ability of the young Kuwaiti educators. Compared to U.S. students, they carry a similar trend and gains in CT concepts and program knowledge. The third reinforcement investigates the ability and preferences between males and females, showing that society and maturity factors are the leading two influencers over Kuwait students' STEM choices, reversing the gender stereotype in Kuwait.
Keywords: Computational thinking